Development of a new grinding system for finishing of hemispherical inside surface. (1st January 2013) - Kotani, H.; Komotori, J.; Naruse, T.; Mizutani, M.; Katahira, K.; Ohmori, H.; Wasa, M.; Sumiya, K.
In this study, in order to apply electrolytic in-process dressing (ELID) grinding for surface finishing process of the sliding parts of metal on metal (MOM) artificial hip joints, a new grinding system to grind the inside surface of a hemispherical cup was developed. In this system, the work piece was pressurised against the centre of the ball shaped grinder with an oscillating pressure pin during the processing. The shape and the radius of the ball shaped grinder were adjusted by using different size abrasive grains. Hemispherical cup-shaped test pieces of 20Cr-2Ni-20Co stainless steel were ground by this grinding system and their surface smoothness was improved. This result suggests that this grinding system is applicable as a surface finishing process of the sliding parts of MOM artificial hip joints.